In Your Face: Startle to Emotional Facial Expressions Depends on Face Direction - Åsli, Ole (Iperception, 2017)
Although faces are often included in the broad category of emotional visual stimuli, the affective impact of different facial expressions is not well documented. The present experiment investigated startle electromyographic responses to pictures of neutral, happy, angry, and fearful facial expressions, with a frontal face direction (directed) and at a 45° angle to the left (averted). Results showed that emotional facial expressions interact with face direction to produce startle potentiation: Greater responses were found for angry expressions, compared with fear and neutrality, with directed faces. When faces were averted, fear and neutrality produced larger responses compared with anger and happiness. These results are in line with the notion that startle is potentiated to stimuli signaling threat. That is, a forward directed angry face may signal a threat toward the observer, and a fearful face directed to the side may signal a possible threat in the environment.